2005
DOI: 10.1093/ndt/gfh764
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase serves as a marker of oxidative stress during single haemodialysis session using two different biocompatible dialysis membranes

Abstract: The biocompatibility of the dialyser affects oxidative stress production during a single dialysis session. The measurement of MPO may serve as a reliable marker of the degree of oxidative stress induced using dialysis membranes of different biocompatibilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 16 publications
7
55
3
1
Order By: Relevance
“…Myeloperoxidase is an important marker of oxidative stress during HD sessions (9,20) and is associated with chronic mild inflammation (21). Interestingly, serum MPO as well as oxAT correlated with female gender in multivariate models in the present study (Tables 1 and 2), whereas another study has not found a significant association between MPO and gender in patients under HD (11).…”
Section: Discussioncontrasting
confidence: 61%
“…Myeloperoxidase is an important marker of oxidative stress during HD sessions (9,20) and is associated with chronic mild inflammation (21). Interestingly, serum MPO as well as oxAT correlated with female gender in multivariate models in the present study (Tables 1 and 2), whereas another study has not found a significant association between MPO and gender in patients under HD (11).…”
Section: Discussioncontrasting
confidence: 61%
“…The results of the present study are in agreement with that of others [9,13] who have also shown a significant rise in MPO after a single dialysis session. MPO is abundantly stored in the primary granulocytes of PMNs and is secreted by activated neutrophils [3].…”
Section: Discussionsupporting
confidence: 93%
“…So far, very few studies [7,8] have demonstrated that dialysis results in neutrophil activation and release of MPO. Also, MPO has been considered as an important pathophysiological factor during the HD process and may serve as a reliable indicator of oxidative stress [9]. Our earlier study carried out on patients with chronic kidney disease who were not on dialysis, has shown that plasma MPO levels declined progressively and significantly with advancing stages of renal failure [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although contradictious results are present, most of other studies support our data. [17][18][19][20] Erythrocytes SOD levels, a parameter of antioxidant defense system, was significantly lower in patients on dialysis therapy than control group and in patients on HD than CAPD (p < 0.001 and p = 0.039, respectively). Statistically no significant difference was observed in levels of GSH-px between patients and control group and between patients on HD and CAPD.…”
Section: Discussionmentioning
confidence: 99%